2006
DOI: 10.1590/s1516-18462006000400012
|View full text |Cite
|
Sign up to set email alerts
|

Relação do pico de fluxo expiratório com o tempo de fonação em pacientes asmáticos

Abstract: OBJETIVO: investigar a possível relação do Pico de Fluxo Expiratório (PFE) com o Tempo Máximo de Fonação (TMF) em pacientes asmáticos. MÉTODOS: a pesquisa enfocou 16 indivíduos com o diagnóstico de asma pura, sendo 9 do gênero feminino e 7 do gênero masculino, atendidos no serviço ambulatorial de pneumologia do Hospital Júlia Kubitschek em BH. A equipe de pneumologia diagnosticou, classificou a asma e realizou o teste PFE. Posteriormente os pacientes foram submetidos à extração de tempo Máximo de Fonação (TMF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
58

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(96 citation statements)
references
References 11 publications
1
36
0
58
Order By: Relevance
“…So, it is shown that the glottal efficiency will depend largely on the respiratory air support of the elderly. These results corroborate those obtained in the study of Rossi et al 18 , who analyzed the relation between expiratory flow peak and the maximum phonation time in asthmatics. The authors defend that one of the reasons to believe that respiratory variables can influence the MPT is that the larynx is mechanically attached to the respiratory tract, allowing it to suffer direct force from breath.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…So, it is shown that the glottal efficiency will depend largely on the respiratory air support of the elderly. These results corroborate those obtained in the study of Rossi et al 18 , who analyzed the relation between expiratory flow peak and the maximum phonation time in asthmatics. The authors defend that one of the reasons to believe that respiratory variables can influence the MPT is that the larynx is mechanically attached to the respiratory tract, allowing it to suffer direct force from breath.…”
supporting
confidence: 92%
“…Thus, it is assumed that there is an association between the two measures. In healthy adults 17 as well as children with asthma 18 , it has already been possible to establish the relationship between the two variables, but in the elderly population, in which a reduction in the values of VC and MPT is expected, it is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be explained by the fact that the MPTP is calculated using only the measurement of the VC and the expected value for each sex 1,19 , but MPT / a / doesn't depend only on VC 1,5,7,9,12,20,21 , but on height, weight and age 7,11 , coordination among respiratory and speech levels and the presence or absence of LD 1,10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors 1,5,8,9,13 used only a stopwatch to define this measure in their research, yet, many programs can provide it, also performing other analyzes. The advantage of using acoustic analysis software is that there is no bias in the time it takes for the evaluator to push the timer button, when beginning and finishing the issue.…”
Section: Discussionmentioning
confidence: 99%
“…This measure integrates functions of the respiratory system, phonatory system and suffers influences from the central nervous system 3 . The MPD offers data from speech functions, exploring the phonatory and expiratory abilities and control [4][5][6] . Its emission should occur at normal pitch and loudness 7,8 .…”
Section: Introductionmentioning
confidence: 99%